Return to Sports Activity following UKA and TKA - Ho, Jason C.; Stitzlein, Russell N.; Green, Charles J.; Stoner, Travis; Froimson, Mark I. (The Journal of Knee Surgery, 2016)
Unicompartmental medial knee arthritis can be successfully treated with either unicompartmental or total knee arthroplasty (UKA or TKA). Active patients often inquire about the relative likelihood of returning to a sport-related activity after surgery. Some advocates of UKA suggest that UKA can lead to a higher rate of return to sports activity postoperatively, but little information is available comparing the outcomes of UKA versus TKA. We identified 33 patients with UKA and 39 patients with TKA with minimum 2-year follow-up (4 ± 1.2 years) who had similar preoperative clinical and radiographic examinations. Clinical evaluation revealed no difference in the number of patients who returned to sports or their satisfaction, but patients with UKA returned to sports more quickly and exhibited better postoperative knee scores than TKA patients.
Keywords: UKA; TKA; return to sports; arthroplasty